Pathogenicity and Pyrenocine Production of Curvularia inaequalis Isolated from Zoysia Grass - Kim, Jin-Cheol (Plant disease, 2000)
Five isolates of Curvularia inaequalis were obtained from blighted leaves of zoysia grass. The optimal growth temperature of the pathogen was 30°C and all isolates caused foliar blighting symptoms on zoysia grass, bent grass, and bermuda grass. Phytotoxic substances were associated with pathogenicity. Two phytotoxins were isolated from liquid cultures of C. inaequalis by ethyl acetate extraction and repeated silica gel column chromatography. On the basis of mass and nuclear magnetic resonance spectral analyses, the compounds were identified as pyrenocines A and B, phytotoxins produced by Pyrenochaeta terrestris. Pyrenocine A caused leaf necrosis in a leaf-wounding bioassay and inhibited growth of all plants tested in a whole plant test. Large crab grass and fall panicum were most susceptible to pyrenocine A. Pyrenocines A and B also caused significant electrolyte leakage from leaf tissues of bermuda grass. Pyrenocine B exhibited much weaker phytotoxic activity than pyrenocine A in all bioassays performed. Both compounds caused leaf tip dieback symptoms in turf grass plants similar to symptoms observed in the field. Thus, pyrenocines A and B are thought to be involved in the development of Curvularia blight disease of turfgrasses caused by C. inaequalis